PENGARUH EARNING PER SHARE (EPS) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ashma Fiya Alfiyyah; Siti Aisyah; Muhammad Nur Abdi (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2026)
This study examines the effect of Earning Per Share (EPS) and Return on Equity (ROE) on the stock prices of property and real estate companies listed on the Indonesia Stock Exchange. The main issue addressed in this research is the decline in the stock prices of property companies following the COVID-19 pandemic. The objective of this study is to determine the influence of Earning Per Share (EPS) and Return on Equity (ROE) on the stock prices of property and real estate companies listed on the Indonesia Stock Exchange. This research employs a quantitative approach, with documentation as the primary method of data collection. A total of ten (10) property and real estate companies were selected as the sample for this study. The findings indicate that Earning Per Share and Return on Equity have a negative and significant effect on stock prices. This research recommends enhancing business strategies to mitigate the negative impacts of EPS and ROE on stock prices. Such strategies may include improving capital structure, increasing operational efficiency, and diversifying business activities to enhance stock attractiveness to investors.Keyword: Stock Price, EPS, ROE